2009
DOI: 10.1007/s00244-009-9367-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of the Fungicide Carbendazim in Tropical Freshwater Microcosms

Abstract: Direct and indirect effects of the fungicide carbendazim on ecosystem structure and functioning were studied B8 weeks after application (nominal concentrations: 0, 3.3, 33, 100, and 1000 lg/L) to outdoor microcosms in Thailand. Direct effects on macroinvertebrates are discussed in detail in a separate article. The present article presents the effects on other end points and discusses the hypothesized ecologic effect chain. Negative treatment effects on the zooplankton community were only recorded for the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…For microorganisms, an indirect effect reported by a few studies is an increase in phytoplankton abundance or biofilm biomass due to fungicide exposure. This effect was observed for fungicides covering a range of MoAs, including azoxystrobin, 111 carbendazim, 120 , 147 chlorothalonil, 125 , 126 fluazinam (i.e., 2,6-dinitro-aniline), 148 organochlorine fungicides (2,4,6-trichlorophenol and pentachlorophenol), 149 , 150 and thiram. 151 The pattern was linked to a reduced grazing pressure by affected invertebrate consumers or, as hypothesized by Staley et al, 152 by microorganisms benefiting from the metabolization of fungicides or organic material set free by dying organisms.…”
Section: Effectsmentioning
confidence: 95%
“…For microorganisms, an indirect effect reported by a few studies is an increase in phytoplankton abundance or biofilm biomass due to fungicide exposure. This effect was observed for fungicides covering a range of MoAs, including azoxystrobin, 111 carbendazim, 120 , 147 chlorothalonil, 125 , 126 fluazinam (i.e., 2,6-dinitro-aniline), 148 organochlorine fungicides (2,4,6-trichlorophenol and pentachlorophenol), 149 , 150 and thiram. 151 The pattern was linked to a reduced grazing pressure by affected invertebrate consumers or, as hypothesized by Staley et al, 152 by microorganisms benefiting from the metabolization of fungicides or organic material set free by dying organisms.…”
Section: Effectsmentioning
confidence: 95%
“…Likewise, this work has a worldwide interest since this species, besides living in temperate ecosystems, is also abundant in the tropics and carbendazim has been extensively used as a fungicide in tropical agriculture and its effects on tropical freshwater zooplankton have been considered, such as studies of whole communities in mesocosms (Daam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…and Bosmina longirostris and calanoid copepodites and cyclopoid nauplii increased in abundance in the treated ponds (Mohr et al, 2008). Daam et al (2010) pointed out that, apparently, the genus Keratella includes the most susceptible representatives of rotifers to fungicides. Other results regarding rotifers showed that Brachionus sp.…”
Section: Zooplankton Communitymentioning
confidence: 97%